2017
DOI: 10.1002/ente.201600498
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Host Polymers for Luminescent Solar Concentrators

Abstract: One of the most important elements of a luminescent solar concentrator (LSC) is the host material. In this work, we investigate the key optical properties of eight polymeric host matrices. Poly(methyl methacrylate) (PMMA) and polycarbonate (PC) based formulations exhibited the lowest internal absorbance within the spectral range of the absorption and emission bands of a red‐emitting fluorescent organic dye (Lumogen Red 305). The dye absorbance was dependent on the host matrix and was higher for the PC‐based fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 28 publications
4
52
0
1
Order By: Relevance
“…The choice of the host/waveguide material employed for the LSC assembly has also a direct effect on efficiency as it can greatly impact the processes of photon harvesting (reflection and scattering losses are matrix-dependent), absorption/emission (photoluminescence quantum yield (PLQY) of the luminophore can be affected by its solubility in the host matrix material), waveguiding/collection at the LSC perimeter (TIR and parasitic absorption by the host matrix are determined by its optical properties) (Kastelijn et al, 2009). Host materials for LSC applications should be designed so as to provide simultaneously a number of desirable features (Zettl et al, 2017), including: suitable refractive index; high transmittance in the visible and near-infrared range; high thermodynamic solubility for the embedded luminescent species; suitable thermal properties (namely, thermo-oxidative stability, and glass transition temperature T g ) compatible with the conditions used for materials processing and with the target application; long-term durability in outdoor contexts.…”
Section: Lsc Operation and Host Materials Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the host/waveguide material employed for the LSC assembly has also a direct effect on efficiency as it can greatly impact the processes of photon harvesting (reflection and scattering losses are matrix-dependent), absorption/emission (photoluminescence quantum yield (PLQY) of the luminophore can be affected by its solubility in the host matrix material), waveguiding/collection at the LSC perimeter (TIR and parasitic absorption by the host matrix are determined by its optical properties) (Kastelijn et al, 2009). Host materials for LSC applications should be designed so as to provide simultaneously a number of desirable features (Zettl et al, 2017), including: suitable refractive index; high transmittance in the visible and near-infrared range; high thermodynamic solubility for the embedded luminescent species; suitable thermal properties (namely, thermo-oxidative stability, and glass transition temperature T g ) compatible with the conditions used for materials processing and with the target application; long-term durability in outdoor contexts.…”
Section: Lsc Operation and Host Materials Requirementsmentioning
confidence: 99%
“…PMMA is by far the most widely employed host polymer for LSCs because of its excellent transparency to visible light and its suitable refractive index (n ≈ 1.5) (Li et al, 2019). Recently, its use as host matrix material in bulk LSCs was benchmarked against other commodity thermoplastics with similarly suitable thermal characteristics [polystyrene (PS), styrene-acrylonitrile (SAN) and different classes of PC] in terms of optical properties, compatibility with the target luminescent species (Lumogen F 305 Red by BASF, LF305 from here on) and resulting optical efficiency (Zettl et al, 2017). It was found that PMMA and PC (compact-disc grade) displayed the highest output irradiance level from the LSC edges, in both cases yielding η opt values of 8.9% with dye doping concentration of 500 ppm.…”
Section: Polymeric Matricesmentioning
confidence: 99%
“…The values of the IPCE (including all optical losses, PV interface losses and the quantum efficiency of the PV cell) were calculated from the equation [Eq. (7)]: [16,[33][34][35]…”
Section: Synthesis Of 47-dibromobenzo[c]mentioning
confidence: 99%
“…To enable an easy process and control the morphology of the optically active centers, poly methyl methacrylate (PMMA) was chosen due to attractive features such as low cost, environmentally friendly nature, high optical transparency [29], high resistance to UV radiation exposure and several chemical treatments, exceptional performance in all-weather conditions and extensive use in construction as a lightweight window material and optical fiber [30]. Moreover, PMMA is an easy material to work with in the laboratory, not presenting any noteworthy risk concerns, which allows high doping concentrations before concentration quenching occurs [31] and transforms them into high-optical-quality transparent matrices with no degradation in their photoluminescence efficiency [30]. Even if PMMA exhibits relatively poor mechanical resistance [31], that can be overcome by the ISs silica nature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PMMA is an easy material to work with in the laboratory, not presenting any noteworthy risk concerns, which allows high doping concentrations before concentration quenching occurs [31] and transforms them into high-optical-quality transparent matrices with no degradation in their photoluminescence efficiency [30]. Even if PMMA exhibits relatively poor mechanical resistance [31], that can be overcome by the ISs silica nature. The combination of ISs and PMMA can result in transparent, flexible, and luminescent materials, presenting fascinating prospects in luminescent photovoltaic applications.…”
Section: Introductionmentioning
confidence: 99%